Superstars of science : The brave, the bold, and the brainy - Grant, R. G.; Basher (New York ; Scholastic, 2015)
"Discover fun facts about the greatest scientists from history through Basher's fresh and unique illustration style. Did you know that Marie Curie used to keep radioactive materials in her pockets? Or that Mendeleyev literally dreamed up his famous periodic table? Superstars of Science tells the stories behind the big ideas in the fields of physics, chemistry, medicine, mathematics, cosmology, earth sciences, and engineering. Read about 40 great scientists including Newton and Einstein who produced theories that explained the way in which the Universe works, Crick and Watson who uncovered the structure of DNA, and Alexander Graham Bell who had the big idea that became the telephone. Each one of these greats of science has had some vital flash of insight that has changed the way we see the world and the way we live. Come meet the superstars of science!"
Keywords: Biography -- Scientists -- History